2019
DOI: 10.1161/circgen.118.002433
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Markers of Inflammation Persist in Children and Adults With Giant Aneurysms After Kawasaki Disease

Abstract: Background: The sequelae of Kawasaki disease (KD) vary widely with the greatest risk for future cardiovascular events among those who develop giant coronary artery aneurysms (CAA). We sought to define the molecular signature associated with different outcomes in pediatric and adult KD patients. Methods: Molecular profiling was conducted using mass spectrometry–based shotgun proteomics, transcriptomics, and glycomics methods on 8 pediatric KD patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…These authors found that the endothelium of the coronary arteries from the myocardial sections of three deceased KD patients were almost completely coated when stained with antibodies against MRP8 or MRP14 (S100A8 or S100A9). Recent investigation using a proteomic approach documented elevated levels of MRP8/14 decades after acute KD in patients with giant aneurysms ( 29 ). The variations in the correlations with CAA development may depend on technical differences in measuring CAA dimensions, but more likely will be determined by statistical power (or lack thereof) because of the small sample size of these studies, the non-prospective study design, and maybe also because of genetic differences in the cohorts tested.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that the endothelium of the coronary arteries from the myocardial sections of three deceased KD patients were almost completely coated when stained with antibodies against MRP8 or MRP14 (S100A8 or S100A9). Recent investigation using a proteomic approach documented elevated levels of MRP8/14 decades after acute KD in patients with giant aneurysms ( 29 ). The variations in the correlations with CAA development may depend on technical differences in measuring CAA dimensions, but more likely will be determined by statistical power (or lack thereof) because of the small sample size of these studies, the non-prospective study design, and maybe also because of genetic differences in the cohorts tested.…”
Section: Discussionmentioning
confidence: 99%
“…Alarmins from the S100 protein family, which are present in the cytoplasm of neutrophils, monocytes and macrophages 82 , also participate in this inflammatory process. Concentrations of circulating S100A8/A9 hetero dimers (calprotectin) and S100A12 are substantially higher in patients with Kawasaki disease during the acute phase than in control patients with other febrile illnesses and decline after IVIG treatment [83][84][85] . After the acute phase of Kawasaki disease, plasma concentrations of S100A8/A9 heterodimers only remain elevated in patients with giant CAAs 84 , highlighting its potential utility as a biomarker to monitor long-term persistence of inflammation.…”
Section: Pathophysiology Of Kawasaki Diseasementioning
confidence: 99%
“…Concentrations of circulating S100A8/A9 hetero dimers (calprotectin) and S100A12 are substantially higher in patients with Kawasaki disease during the acute phase than in control patients with other febrile illnesses and decline after IVIG treatment [83][84][85] . After the acute phase of Kawasaki disease, plasma concentrations of S100A8/A9 heterodimers only remain elevated in patients with giant CAAs 84 , highlighting its potential utility as a biomarker to monitor long-term persistence of inflammation. S100A12 also contributes to the acute inflammatory response by directly stimulating monocytes to produce IL-1β, which in turn activates coronary endothelial cells 85 .…”
Section: Pathophysiology Of Kawasaki Diseasementioning
confidence: 99%
“…Otherwise, a large aneurysm can develop and lead to mortality and morbidity. Levels of calprotectin are elevated in pediatric patients with giant coronary artery aneurysms one-year post-KD [10]. Improved diagnostic tools and the development of riskspecific anti-inflammatory treatments have enabled intervention research for people at ultra-high risk.…”
Section: Introductionmentioning
confidence: 99%